Complementary and alternative medicines usage in bipolar patients from Argentina and Colombia: Associations with satisfaction and adherente to treatment - Strejilevich, Sergio (2013)
BACKGROUND: The use of Complementary and Alternative Medicines (CAM) has been reported by around half the patients undergoing medical treatment for chronic conditions. CAM use could be higher in people affected by bipolar disorders (BD). Some questions about CAM use in BD have not been investigated enough. We report here the results of an anonymous survey on CAM-use conducted among BD outpatients of two centers located in Argentina and Colombia. METHODS: an anonymous self-survey was administrated to bipolar euthymic outpatients treated at each center. The survey included a self-report measure of adherence to psychiatric treatment and a modified version of CGI to asses satisfaction with the current treatment. RESULTS: 200 patients completed the survey. Although samples differ in socio-economic profile, they do not differ in their reported CAM-usage (more than 40%). CAM-usage did not modify the adherence or satisfaction with the psychiatric treatment reported level. Thirty eight percent of those who were still resorting to CAM failed to inform it to their clinician. CAM-usage was rated as "useful" or "very useful" by 52% of patients. LIMITS: adherence to current medical treatment and satisfaction with current treatment were investigated by a self-reported instrument. DISCUSSION: the prevalence of CAM usage found is similar to that of other studies. CAM usage seems to be ubiquitous, which takes to posit that a subgroup of patients may be in need of treatment with greater magical-religious components. Half of these patients were reluctant to disclose CAM use. Clinicians may need to consider coexistence between "traditional" treatments and CAM for these patients.